Development of Information Service Media to Reduce Student Learning Saturation at SMA Negeri 15 Padang - Meilinda, Shinta (Holistic Science, 2022)
This research is a dilator behind the existence of students who have low learning saturation, as well as the lack of learning media methods provided by the BK teacher to reduce the learning saturation of these students. This study aims to determine: 1) Profile of the level of learning saturation of students in class XI MIPA. 2) Designing development media to reduce the boredom of learning based on Information Technology (IT) which is acceptable theoretically and practically.  This study uses a quantitative descriptive research approach. The population in this study were students in class XI MIPA SMA Negeri 15 Padang 234 students. The number of samples is 70 students. The sampling technique is simple random sampling. The instrument used is a questionnaire. Meanwhile, for data analysis using Microsoft Excel.  Based on the results of this study, it is revealed that: 1) For the profile of the level of learning saturation of students in class XI MIPA is in the medium category, 2) Media that has been validated by theoretical and practical experts is categorized as "Very acceptable" and suitable for use. Based on the results of this study, it is recommended for BK teachers to use media that have been developed by IT by researchers and for further researchers it is recommended to test the effectiveness of IT-based media designs to reduce student learning saturation so that effective guidance and counseling services can be implemented in schools.